ANALISIS YURIDIS TERHADAP PENANGGULANGAN TINDAK PIDANA PENYEBARAN BERITA BOHONG DAN MENYESATKAN - Yang, Roxelina; Svinarky, Irene (SCIENTIA JOURNAL, 2019)
The spread of false and misleading news (hoax) itself has a definition of a news or statement that has invalid information or false news that has no certainty that is deliberately disseminated to make the situation excited and cause fear. If previously the spread of false and misleading news (hoaxes) was disseminated through SMS or e-mail with a lot, then the hoaxes are currently circulating more on social media. Related to the formulation of Article 28 paragraph (1) of the ITE Law which uses the phrase "spreading false news", actually in the provisions of Article 390 of the Criminal Code (KUHP), even though the formulation is slightly different, the phrase "broadcast false news" is used. In the application of article 28 paragraph (1) of the ITE Law there must be consumer losses as material requirements and also in applying the article, the social networking service providers cannot be charged with the provisions of article 55 of the Criminal Code as participating in the spread of false news carried out by the perpetrators through social networks.